The development of China's exports: Is there a decoupling from the EU and the United States? - Volker Brühl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2024)
Some observers warn that a high level of economic dependence on China could negatively affect the economic resilience of Western economies and therefore recommend reducing such dependence by gradually decoupling from China. On the other hand, industry leaders emphasise the economic importance of China and warn against any kind of trade conflicts. Against this background, we briefly analyse the development of China's export strategy. We find that the export intensity of the Chinese economy is diminishing and that exports are becoming more diversified overall. In addition, the relative importance of the United States and the European Union as export markets has been reduced, indicating a gradual decoupling of China from Western economies. Conversely, we find that exports to China have become more important, both for the EU and the United States. Although the figures remain at a non-critical level, Europe's export activities could be more diversified as well.
Keywords: F01; F14; O1; O53; 330